UTILISATION OF DIGITAL MARKETING BY RURAL ENTREPRENEURS OF SOUTH ODISHA. (CAHIERS MAGELLANES-NS, 2024)
Digital Marketing is among the greatest tools used for marketing in the modern world. Not only it has brought down the marketing expenses through its efficiency but has also helped the entrepreneurs in engaging with the customers more effectively. It also helps in collecting and analysing the data on customers behaviour so that the entrepreneurs can make more efficient strategies for attainment of their business goals. (Sheoliha et al 2023).  Various studies and research has been done upon use of Digital marketing by entrepreneurs. However, the utilisation of Digital marketing options by rural micro entrepreneurs in India is still a field to be explored.Purpose of study: Presented study aims at Identifying the factors effecting the utilisation of Digital Marketing for business promotion by micro entrepreneurs of the rural areas of South Odisha.Methodology used: The study employs the combination of UTAUT and TOE model. It is done based on the responses of 386 respondents from the region. The data is then subjected to Exploratory factor analysis for factor extraction and regression analysis for hypothesis testing.Outcome: The outcome of the study suggests that the factors like Performance expectancy, Effort expectancy, Technological factors, Organisational factors, and Environmental factors impact the utilisation of Digital marketing by the micro entrepreneurs of the rural areas of South Odisha.